Le Stanze - Bonito Oliva, Achille; Castello Colonna, Genazzano (Firenze : Centro Di, 1979)
Anselmo, Giovanni ; Boetti, Alighiero ; Calzolari, Pier Paolo ; Chia, Sandro ; Clemente, Francesco ; Cucchi, Enzo ; De Maria, Nicola ; Kounellis, Jannis ; Merz, Mario ; Merz, Marisa ; Mochetti, Maurizio ; Paladino, Mimmo ; Paolini, Giulio ; Penone, Giuseppe ; Pisani, Vettor ; Salvo ; Zorio, Gilberto
Le Stanze, Castello Colonna, Genazzano, 30 Novembre 1979 - 29 Febbraio 1980
boek